El imaginario religioso en el discurso periodístico del 11-S - Pou Amerigo, María José (Estudios sobre el Mensaje Periodístico, 2002)
The first chronicles and journalistic commentaries about September 11th include religious references in a process of sacred rites of the day-to-day things that contains elements of the religious experience: rites, sacred spaces or sacred objects. The means will add, therefore, the mythical or legendary stories. The contexts of these terms are the emotional spiritual experience, the struggle against the heretics or the secular faith in the democratic principles.